WARNA BUDAYA JAWA DALAM CERPEN “MACAN LAPAR” KARYA DANARTO - Yosi Wulandari; Muhammad Alfian Hermawan (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2021)
The use of a short storytelling style requires the author's expertise to play on the use of specific languages and certain styles. Likewise with danarto, in the short story "Tiger Hungry" it is assumed to have an interesting style in the use of sentence and discourse style so it needs to be explored further. The purpose of this study is to describe the sentence style and discourse style contained in the short story "Macan Lapar" by Danarto. This research uses descriptive method with a statistical approach. The theory used is the concept of style by Ali Imron Al Ma'rif. The results of this study indicate that the use of sentence styles and dominant discourses shows Danarto's characteristics in conveying the contents of the story with an emphasis on the setting of the story with the intention of explaining how charismatic a Princess Solo is so as to be able to attract foreign youth. In addition, Danarto's love for Javanese culture was very thick so that regional color became an ornament in this short story.